Gaya Kepemimpinan Partisipatif dan Inovasi Organisasi di Perusahaan BUMN Indonesia - Syahriful Ahyar; Reski Apriyani; Nanda Herlianur; Putri Rahmawati; Viola Augustia Putri; Naomi Boru Tobing (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines participatory leadership styles and their influence on organizational innovation in state-owned enterprises (SOEs) in Indonesia. Participative leadership involves subordinates actively in the decision-making process, which contributes to increased motivation, productivity, and individual performance within the organization. Using a qualitative descriptive approach, this study explores the concepts and practices of leadership and innovation applied in SOEs. The results show that participatory leadership not only increases employee engagement but also creates a collaborative and innovative work environment. By involving different generations in decision-making, leaders can leverage the experience of senior generations and fresh ideas from younger generations, thereby encouraging more creative and relevant innovation. The implications of this research indicate that the application of a participatory leadership style is very important for SOEs to strengthen their competitiveness, adapt to market changes, and make a significant contribution to national development. This research provides valuable insights for leadership development and innovation strategies in the SOE sector in Indonesia.